Determination of mercury in soil and water from a gold mining area in Karang Jaya Sub-district, Musi Rawas Utara, Indonesia - Amallia, Ra Hoetary Tirta; Ibrahim, Eddy; Irfannuddin, Irfannuddin; Hariani, Poedji Loekitowati (Brawijaya University, 2024)
The present study focuses on the assessment of Hg distribution in both soil and water samples from the small-scale gold mining region of Karang Jaya Sub-district, Musi Rawas Utara Regency, South Sumatra Province. For over 30 years, this region has witnessed persistent utilization of mercury as an amalgam for gold extraction. The investigation encompasses an analysis of total mercury levels in soil samples obtained from Sukamenang, Muara Batang Empu, and Terusan Villages. As a comparative reference point devoid of gold mining activities, the neighboring Muara Lakitan Village was selected. The obtained results indicate a moderate to strong contamination level across the 30 sampled locations based on the Geoaccumulation Index (Igeo), with an average Igeo value of 2.6. Furthermore, Pollution Load Index (PLI) and Contamination Factor (CF) values demonstrate high contamination. Conversely, analysis of river water samples from 30 stations along the Rupit River reveals that most of the samples comply with quality standards (<0.0005 mg/L), with an average value at 0.000322 mg/L; only four stations exhibit total Hg concentrations surpassing regulatory thresholds. All soil and river water samples from the control area (10 stations) exhibited no signs of pollution. Appropriate investments in technology, finance, and technical skills are needed to reduce mercury pollution due to small-scale gold mining activities.